Figurative Language used on @Poets Instagram Social Media: A Pragmatics Analysis - sri bulan (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
Figurative language is language that used words or expressions which has different meanings from literal interpretations. Every figurative language is used in literary works especially poem, to better understand its intentions and messages. It also used to express feeling like a happiness, grieving, heartbreak, and disappointment of the author. This study aims to describe the types of figurative language and the pragmatic effects used in @poets Instagram social media. This study used the Abrams theory in which figurative language consists of alliteration, allusion, assonance, hyperbole, imagery, irony, metaphor, metonymy, onomatopoeia, paradox, personification, simile, and synecdoche. This study used descriptive qualitative method. The data of this study are 16 poem posts from the @poets Instagram account and the writer only took data uploaded from October 2, 2019 to November 19, 2019. Data is collected by using several steps: opening, reading, screenshoting, and coding. The writer used some steps for techniques of analysis data, as follows: presenting the data, describing the context, interpreting the data, and making conclusion. The result of this study is figurative language that contains on @poets Instagram Social Media, there are, Assonance 3 data, Hyperbole 6 data, Personification 3 data and Simile 4 data. Also, 5 kinds of pragmatic effects that are used namely Expressing Negativity, Enchancing Meaning, Objectivication, Identification, and Emotion Expression.